VIPCT- Vascularized Interpostional Periosteal Connective Tissue Flap - John, Ligi Elsa; Rodrigues, Silvia; Mitra, Dipika; Shah, Rohit; Vijayakar, Harshad; Shetty, Gaurav; Prithyani, Saurabh (International Journal For Research In Health Sciences And Nursing, 2018)
Nowadays esthetics plays an important role in dentistry along with function of the prosthesis. Various soft tissue augmentation procedures are available to correct the ridge defects in the anterior region. A new technique, vascularized interpositional periosteal connective tissue (VIP-CT) flap, has been introduced, which has the potential to augment predictable amount of tissue and has many benefits when compared to other techniques.